Biosynthesis of LC-PUFA in Ruditapes philippinarum: Cloning and tissue distribution of Fad and Elovl, and effects of microalgae diets varied in LC-PUFA composition on their expressions and fatty acids profile of this bivalve - Wu, Kaibin; Ran, Zhaoshou; Wu, Shurong; Xie, Haixuan; Li, Yanrong; Liao, Kai; Xu, Jilin; Yan, Xiaojun (Frontiers in Marine Science, 2023)
To reveal the biosynthetic pathway of long-chain polyunsaturated fatty acids (LC-PUFA) in Ruditapes philippinarum, herein, two fatty acid desaturases (Fads, including one Δ5 Fad and one Δ6 Fad-like) and three elongases of very long-chain fatty acids (Elovls, including one Elovl2/5 and two Elovl4-like) genes were firstly cloned from this bivalve and their tissue distributions were examined. Results showed that the newly cloned Fads and Elovls contained the corresponding conserved functional domains and clustered closely with their orthologs, respectively. Meanwhile, they were expressed significantly higher in the digestive glands and intestine. Subsequently, to further understand the LC-PUFA biosynthesis in R. philippinarum, the effects of dietary LC-PUFA on Fad and Elovl expressions and the fatty acid (FA) profile in this bivalve were investigated by feeding with three microalgae varied in LC-PUFA compositions [including Chlorella sp. (rich in 18:2n-6 and 18:3n-3), Chaetoceros calcitrans (rich in eicosapentaenoic acid, EPA), and Isochrysis galbana (rich in docosahexaenoic acid, DHA]. Results showed that, throughout the experiment, the expressions of Fad and Elovl were significantly up-regulated in the visceral mass (digestive glands and intestine) of R. philippinarum fed with Chlorella sp., while no significant changes or slightly decreases were observed in those fed with I. galbana. Furthermore, in those fed with C. calcitrans, the expressions of Fad were not significantly changed, whereas the expressions of Elovl were firstly up-regulated but then restored to its initial level at the end of experiment. These results suggested that R. philippinarum could modulate Fad and Elovl expressions to adapt to the dietary LC-PUFA composition. The FA analysis showed that a significantly higher amount of DHA and EPA was found in the R. philippinarum fed with I. galbana and C. calcitrans, respectively, which reflected well of the dietary FA. However, the R. philippinarum fed with Chlorella sp. exhibited a significant decrease of 18:2n-6 and 18:3n-3 but with a significant increase of their products such as 20:3n-6 and 22:5n-3, indicating that R. philippinarum had a certain capacity for LC-PUFA biosynthesis. Collectively, this study provided valuable insights into the biosynthesis of LC-PUFA in R. philippinarum.